Preparing towards Preventing and Containing an Ebola Virus Disease Outbreak: What Socio-cultural Practices May Affect Containment Efforts in Ghana? - Philip Baba Adongo; Philip Teg-Nefaah Tabong; Emmanuel Asampong; Joana Ansong; Magda Robalo; Richard M Adanu (PLoS Neglected Tropical Diseases)
Background Ebola Virus Disease (EVD) is a condition with high fatality. Though the disease is deadly, taking precautions to reduce contact with infected people and their secretions can prevent cross- infection. In the 2014 EVD outbreak, socio-cultural factors were identified to be responsible for the spread of the disease in the three most affected countries in West Africa. In this light, we undertook this study to identify socio-cultural factors that may influence the prevention and containment of EVD in Ghana and ways to address such practices. Methods We conducted a descriptive qualitative study in five regions in Ghana. Twenty-five focus group discussions (5 in each region) with community members (4 in each region) and nurses (1 in each region) were conducted. In addition, forty (40) in-depth interviews were conducted with various stakeholders and opinion leaders; eight in each region. All interviews were recorded using a digital voice recorder and transcribed. With the aid of Nvivo 10 for windows, we analyzed the data using framework analysis. Results We found that socio-cultural practices, such as care of the body of dead and burial practices, widowhood rites and anointing children with water used to rinse the dead, were common. These practices require individuals coming into direct contact with either the dead or items used to take care of the dead. Social norms also require frequent handshakes in all social gatherings such as funeral, and religious congregations. We also found that self-medication (using herbs and orthodox medications) was a common practice. People use both biomedical and non-orthodox health outlets either simultaneously or in sequence in times of ill-health. Conclusion The study concludes that high risk socio-cultural practices were common among Ghanaians and generally perceived as indispensable. These high risk practices may hinder containment efforts in the event of an outbreak. Community leaders should be engaged in any social mobilization to modify these practices as part of preparation efforts.